Preparation of monodispersed sulfur nanoparticles-partly reduced graphene oxide-polydopamine composite for superior performance lithium-sulfur battery. (April 2017) - Zhang, Yiyong; Li, Kun; Huang, Jingxin; Wang, Yunhui; Peng, Yueying; Li, He; Wang, Jing; Zhao, Jinbao
Abstract: Lithium-sulfur battery has received extensive attention because of its high energy density, but its practical application has been limited by several problems such as short cycle life and low efficiency. In this study, we prepare monodispersed sulfur nanoparticles (S NPs) on partially reduced graphene oxide (S-prGO) during reduction of graphene oxide by spray method. The S-prGO composite is then recombined with polydopamine (PDA) to get the S-prGO-PDA composite. The S-prGO-PDA composite exhibits great cycling stability, coulombic efficiency and capacity retention. When charge-discharge at current density of 200 mA g −1, the specific capacity is 1122 mAh g −1 at the first discharge and 647 mAh g −1 after 100 cycles, with stable coulombic efficiency of 98%. Graphical abstract: